Smoking status and the efficacy of remote ischaemic conditioning: a secondary analysis of the RICAMIS trial - Yu Cui; Hui-Sheng Chen; Xian-Wen Zhang (Stroke and Vascular Neurology)
Background Remote ischaemic conditioning (RIC) is a potential non-invasive neuroprotective strategy, but it remains unclear whether its efficacy is influenced by smoking status. This study explored the impact of smoking status on the therapeutic effect of RIC in patients with acute moderate ischaemic stroke through a post hoc subgroup analysis.Methods Based on the data from the Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke trial, 1717 patients with moderate stroke (National Institutes of Health Stroke Scale score 6–16) who did not undergo reperfusion therapy were included and categorised into current smokers (n=505) and non-smokers (n=1212) based on their smoking status. Patients were randomly assigned to receive either RIC (administered twice daily for 14 days) or standard treatment. The primary outcome was excellent functional prognosis at 90 days (modified Rankin Scale, mRS scores 0–1). Multivariable regression analysis was used to evaluate the interaction between smoking status and RIC.Results Among non-smokers, RIC significantly increased the proportion of patients achieving mRS 0–1 at 90 days (69.1% vs 62.8%; adjusted OR 1.487, 95% CI 1.143 to 1.936; p=0.003). Among current smokers, there was no significant difference in the proportion of mRS 0–1 at 90 days compared with the control group (64.1% vs 62.1%; adjusted OR 1.154, 95% CI 0.791 to 1.684; p=0.46). The interaction analysis revealed no significant association between smoking status and RIC efficacy (P for interaction=0.50).Conclusions In this analysis, RIC significantly improved the excellent functional prognosis of non-smoking stroke patients, but had no significant benefit for current smokers, suggesting that smoking may attenuate RIC efficacy.Trial registeration number NCT03740971.